Pharmacokinetic changes and therapeutic drug monitoring of lamotrigine during pregnancy. Issue 7 (18th May 2019) - Ding, Ye; Tan, Xiaoping; Zhang, Shuo; Guo, Yang
Abstract: Objectives: To evaluate the pharmacokinetic changes in lamotrigine (LTG) from prepregnancy to postpartum and to assess the impact of therapeutic drug monitoring (TDM) on seizure management during pregnancy in a Chinese population. Methods: A series of women who were on LTG monotherapy before conception or during pregnancy were included in this retrospective study. The clinical characteristics of the mothers and fetuses were collected. The apparent clearance (AC) and the ratio to target concentration (RTC) were calculated for each trimester or for each month. RTCs were compared between patients with and without an increase in the frequency of seizures. A receiver operating characteristic curve to determine the RTC threshold, which predicts increased seizure frequency best, was drawn. Results: A total of 12 patients and their 12 pregnancies were reviewed retrospectively. AC increased by 82.5% during the first trimester ( p  = 0.0343), 203.2% during the second trimester ( p  = 0.0010), and 197.0% during the third trimester ( p  = 0.0061) compared with the prepregnancy level. The value returned to the prepregnancy level after delivery. Seven patients who had adequate baseline information were included to examine the association between serum LTG concentration and seizure frequency. The RTC values of patients with and without an increased frequency of seizures were significantly different ( p  = 0.0164), and increased seizure frequency was associated with a lower RTC. An RTC < 0.64 was a predictor of deteriorating seizures. Conclusions: The pharmacokinetic changes in LTG during pregnancy displayed marked interpatient variation. TDM can support a rational treatment plan for LTG use during pregnancy. We recommend regular monitoring of LTG serum concentrations from prepregnancy to postpartum. Abstract : Pregnancy influences the pharmacokinetics of lamotrigine. A reduction in ratio to target concentration (RTC) leads to worsening seizures. RTC < 0.64 was a predictor of deteriorating seizures. A dosage adjustment is necessary for pregnant women when RTC < 0.64.